2009
DOI: 10.1186/1471-2164-10-392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel endogenous antisense transcripts by DNA microarray analysis targeting complementary strand of annotated genes

Abstract: Background: Recent transcriptomic analyses in mammals have uncovered the widespread occurrence of endogenous antisense transcripts, termed natural antisense transcripts (NATs). NATs are transcribed from the opposite strand of the gene locus and are thought to control sense gene expression, but the mechanism of such regulation is as yet unknown. Although several thousand potential sense-antisense pairs have been identified in mammals, examples of functionally characterized NATs remain limited. To identify NAT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…31 Today endogenous antisense transcription is recognized as pervasive and as an integral cellular activity. 32,33,34,35 The regulatory potential of antisense transcripts was immediately recognized, 36 and their main activity was initially linked to interference with protein translation. 37,38 However, more recent observations suggest an important role of natural antisense transcripts in the regulation of gene transcription by epigenetic modification of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…31 Today endogenous antisense transcription is recognized as pervasive and as an integral cellular activity. 32,33,34,35 The regulatory potential of antisense transcripts was immediately recognized, 36 and their main activity was initially linked to interference with protein translation. 37,38 However, more recent observations suggest an important role of natural antisense transcripts in the regulation of gene transcription by epigenetic modification of chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to determine whether these sense-antisense (S/AS) pairs are conserved in human, especially as a very short (focal) region of genome amplification in human chromosome 12q23.1 that only contains the genes ELK3 and PCTK2 occurs at a significantly high frequency among 3131 cancer specimens ((Beroukhim et al, 2010); http://www.broadinstitute.org/tumorscape). A large proportion of S/AS pairs are co-expressed (Ge et al, 2008; Katayama et al, 2005; Sun et al, 2005) and bioinformatic studies have found many examples of exon-overlapping S/AS pairs conserved between mouse and human (Numata et al, 2007; Numata et al, 2009; Okada et al, 2008). This suggests that gene expression can be regulated by the formation of S/AS perfectly complementary double-stranded RNA (dsRNA; (Numata et al, 2007; Sun et al, 2005; Werner et al, 2009)), the latter being detectable by RNase protection assays (Munroe and Zhu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we were able to detect the expression of novel antisense RNAs, which were not detected by using cDNA sequences [11]. These AFAS probes were spotted onto microarray slides and used in our microarray platform to generate expression data for the analysis of antisense transcripts.…”
Section: Introductionmentioning
confidence: 99%